Endolaser for facial rejuvenation: An narrative review (Research, Society and Development, 2023)
Objective: to evaluate, through an integrative review, how it is used and what are the advantages and disadvantages of using the endolaser in facial rejuvenation. Methods: a review was carried out in various media available in online databases, in the format of scientific articles, referring to the topic within the criteria, published in the period between 2017 and 2022, languages ​​Portuguese, English and Spanish. Results: 123 citations were found, after excluding duplicates, a total of 61. The title and abstract were analyzed, 40 citations were excluded and 31 were selected for reading. 10 were excluded for not meeting the criteria, 20 were included in the review. Final Thoughts: This non-invasive laser therapy technique can reduce facial wrinkles and expression lines, improve skin texture and tone. Therefore, the endolaser stimulates collagen formation, increases the thickness of the dermis and makes the skin firmer.